REFLECTIONS ON PROVISION OF PRIMARY EDUCATION AND WAY FORWARD IN NIGERIA - Matthew, Ige Akindele (LPPM Undiksha, 2019)
Primary education is an important stage in the education process, being the foundation for other stages. When the foundation of a building is weak, such building stands the risk of collapse in future, but will stand the test of time if it is strong. Primary education provides opportunity for a child to acquire knowledge, skills, traits, and values that can make him/her excel at the secondary and tertiary levels. Unfortunately, there are unresolved issues in its provision in Nigeria. In this paper, inadequate access to it, wastage in its provision, unstable curriculum, teaching of subjects by a teacher, unstable management, among other issues, are examined. The paper recommend the orientation of parents and guardians, strong commitment of government in funding and resource provision, among others, to salvage the situation and move primary education forward from the status quo